2012
DOI: 10.1108/13565361211237716
|View full text |Cite
|
Sign up to set email alerts
|

The bulk alloy microstructure and tensile properties of Sn‐1Ag‐0.5Cu‐xAl lead‐free solder alloys (x=0, 1, 1.5 and 2 wt.%)

Abstract: Purpose -The purpose of this paper is to investigate the effect of Al addition on the bulk alloy microstructure and tensile properties of the low Ag-content Sn-1Ag-0.5Cu (SAC105) solder alloy. Design/methodology/approach -The Sn-1Ag-0.5Cu-xAl (x ¼ 0, 1, 1.5 and 2 wt.%) bulk solder specimens with flat dog-bone shape were used for tensile testing in this work. The specimens were prepared by melting purity ingots of Sn, Ag, Cu and Al in an induction furnace. Subsequently, the molten alloys were poured into pre-he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 22 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…The literature has reported that the primary CuSn phases related to Al-added SAC solder alloys are inhibited, and the groups of Al content suppress the CuSn steps It was observed that β-Sn, CuAl, and SnCu phases were formed in regions close to the Cu 6 Sn 5 phase. When the SEM analyses were examined, the intermetallic components formed at the interface became more prominent as the temperature value increased for each lead-free solder alloy [33][34][35].…”
Section: Morpholpgy and Elemental Analysismentioning
confidence: 99%
“…The literature has reported that the primary CuSn phases related to Al-added SAC solder alloys are inhibited, and the groups of Al content suppress the CuSn steps It was observed that β-Sn, CuAl, and SnCu phases were formed in regions close to the Cu 6 Sn 5 phase. When the SEM analyses were examined, the intermetallic components formed at the interface became more prominent as the temperature value increased for each lead-free solder alloy [33][34][35].…”
Section: Morpholpgy and Elemental Analysismentioning
confidence: 99%